A Correction and Comments on “Multi-Scale Deep Neural Network (MscaleDNN) for Solving Poisson-Boltzmann Equation in Complex Domains CiCP, 28 (5): 1970–2001, 2020” (Communications in Computational Physics, 2023)
This note provides a correction of a missing weight constant in theMscaleDNN formula and some comments on the performance of the corrected algorithm.
Keywords: Multi-scale DNN; PDE solver; deep learning.